Green procurement - Molthan-Hill, Petra (Henry Stewart Talks, 2011)
Financial benefits of green procurement?, Content, Business sustainability and its dimensions, Sustainable development, Sustainable procurement, Climate Change, Demand review, Freight, CO2 emissions, Environmental score sheet, Industrial ecosystem, The seven steps to procurement heaven, References